El gasto real promedio per cápita y la canasta básica de consumo en el Perú en el periodo post pandemia 2020 - Izquierdo Gómez, Julio Kenny (2023)
Poverty levels have been exacerbated by the COVID-19 pandemic in Peru and the world, considerably increasing the number of vulnerable people. The expense average real monthly per capita income is an indicator of well-being. The objective of this research is to analyze the average real monthly per capita spending and the basic consumption basket in Peru in the post-pandemic period 2020. Taking this objective into consideration, this Quantitative-type, Descriptive-level study is carried out. and non-experimental design. The research concludes that the average real spending per capita in Peru contracted in the post-pandemic 2020 period by -16.08%, reducing to S/. 673.00. The analysis of the average real expenditure by natural region shows that the Coast showed a greater reduction compared to the mountains and the Jungle, reducing by -17.90% to S/. 761.00; value that is above the national average which was S/. 673.00. The monthly average per capita real expenditure was mainly concentrated in the consumption group Foods Consumed Within the Home, being S/. 212.00, which represents 31.50% of the total, consistent with the measures applied by the government with the closure of a restaurant due to a pandemic. On the other hand, the most important reduction in average spending occurred in the Food Consumed Outside the Home group, having fallen to S/. 54.00 (-47.70%).